2013
DOI: 10.12669/pjms.292.3149
|View full text |Cite
|
Sign up to set email alerts
|

Adherence of healthcare professionals to American Diabetes Association 2004 guidelines for the care of patients with type 2 diabetes at peripheral diabetes clinics in Karachi, Pakistan

Abstract: Objective: To observe the adherence of Healthcare Professionals to American Diabetes Association (ADA) 2004 guidelines for the care of patients with type 2 diabetes at Peripheral Diabetes Clinics (PDCs) in Karachi, Pakistan. Methodology: The study was conducted using a retrospective medical chart review of patients with type 2 diabetes at four PDCs in four townships of Karachi district from January 2005 to December 2006. Entire medical records of patients were evaluated for the evidence of documentation of tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…It has been clearly shown that the use of guidelines is associated with better prognosis, achieving target goals for HbA1c, blood pressure, renal function, and lipid profiles, as well as greater patient's satisfaction than when they are not used [ 12 14 ]. However, the adherence of healthcare professionals to recommendations of CPGs is unsatisfactory, with deficiencies in most areas of diabetes care and follow-up [ 15 19 ]. Barriers reported include lack of awareness, familiarity or agreement with the content, poor understanding of the need for change to overcome the inertia of normal practice, differences in the goals between clinicians and patients, and a number of external constraints associated with deficiencies in equipment and space, shortage of time, staff, and financial resources [ 20 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been clearly shown that the use of guidelines is associated with better prognosis, achieving target goals for HbA1c, blood pressure, renal function, and lipid profiles, as well as greater patient's satisfaction than when they are not used [ 12 14 ]. However, the adherence of healthcare professionals to recommendations of CPGs is unsatisfactory, with deficiencies in most areas of diabetes care and follow-up [ 15 19 ]. Barriers reported include lack of awareness, familiarity or agreement with the content, poor understanding of the need for change to overcome the inertia of normal practice, differences in the goals between clinicians and patients, and a number of external constraints associated with deficiencies in equipment and space, shortage of time, staff, and financial resources [ 20 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Only 42% underwent the recommended foot examination and only 20% got lifestyle recommendations [9]. A Pakistani study in 2005 revealed that only 30% of the diabetics got an eye examination, and HbA1c levels were recorded for only 44% of the included diabetics [10]. Another American study revealed that only 7% of 42 837 people diagnosed with DMT2 were monitored entirely correctly for HbA1c, according to ADA guidelines, for one year [11].…”
Section: Introductionmentioning
confidence: 99%
“…Haemoglobin A1c levels were recorded in 44% of the patients and fasting blood sugar was checked in 50%. 3 Another study done in Mirpur, Azad Kashmir, Pakistan, in 2012–2013 checked the diabetic preventive care recommendations by physicians. The results revealed that 39% of the patients had not been properly counselled about required lifestyle changes, and that 68% had not received information on prevention of diabetic complications.…”
Section: Introduction/backgroundmentioning
confidence: 99%
“… 7 8 There is a lack of national diabetic guidelines and standardised evidence-based care in Pakistan. 3 4 In a study done in Rawalpindi, Pakistan, only 7% of the physicians were following diabetic guidelines completely. 9…”
Section: Introduction/backgroundmentioning
confidence: 99%